The Added Value of Patient Engagement in Early Dialogue at EMA: Scientific Advice as a Case Study - Murphy, Aisling; Bere, Nathalie; Vamvakas, Spiros; Mavris, Maria (Frontiers in Medicine, 2022)
The European Medicines Agency provides Scientific Advice to medicines developers and patient input has been an integral part of this process for many years. As end users of medicines, patients bring their perspectives to many different processes along EMA's regulatory pathway, complementing the scientific expertise. While the value of including patients has been well-demonstrated over the years, requests for evidence of their impact continue. Using Scientific Advice as a case study, data was collected over a four-year period to assess the number of patients involved, where they contributed, as well as the impact and added value of their input. In this paper, we show that patients' contributions have a tangible impact on the recommendations provided to developers and in over half of the cases, this led to further discussion on relevant patient perspectives. These data provide quantitative evidence of the value of patient input in medicines development and supports EMA's continued inclusion of their voice throughout the medicine's lifecycle.